Effectiveness of Contextual Teaching and Learning (CTL) through Differentiated Instruction on Students’ Critical Thinking Skills in Economics - Nisa', Nadia Fikrotun; Prakoso, Albrian Fiky; Irawan, Nico (IKIP Widya Darma Surabaya, 2024)
Objective: This study intends to analyze the effectiveness of CTL through differentiated instruction in students' critical thinking skills in economics subjects at one of Surabaya’s high schools. Method: Using a quasi-experimental design that compares the experimental with the control class using pre- post-test activities, through a non-equivalent control group design. The experimentation was carried out over 4 meetings involving 2 classes in class X consisting of an experimental class (CTL through differentiated instruction) and a control class (PBL through conventional learning strategies). Pre- post-test data were collected, and ANOVA was used to analyzed the results. Results: Based on ANOVA, the critical thinking skills outcomes of students who received CTL treatment were higher compared to students who received PBL treatment. So that CTL learning through differentiated instruction is effectively used in upgrading students' critical thinking skills in economics subjects. Novelty: The novelty of this research when compared with existing research is by implementing CTL learning in collaboration with differentiated instruction to improving students' critical thinking skills, especially in economics studies. Considering that differentiation instruction is a new learning strategy that can be collaborated with learning models in schools that have implemented the Curriculum Merdeka, this shows the fact that this research has not been found by many other researchers before